Characterization of Syntenin, a Syndecan-binding PDZ Protein, as a Component of Cell Adhesion Sites and Microfilaments - Zimmermann, Pascale (The American Society for Cell Biology, 2001)
Syntenin is a PDZ protein that binds the cytoplasmic C-terminal FYA motif of the syndecans. Syntenin is widely expressed. In cell fractionation experiments, syntenin partitions between the cytosol and microsomes. Immunofluorescence microscopy localizes endogenous and epitope-tagged syntenin to cell adhesion sites, microfilaments, and the nucleus. Syntenin is composed of at least three domains. Both PDZ domains of syntenin are necessary to target reporter tags to the plasma membrane. The addition of a segment of 10 amino acids from the N-terminal domain of syntenin to these PDZ domains increases the localization of the tags to stress fibers and induces the formation of long, branching plasma membrane extensions. The addition of the complete N-terminal region, in contrast, reduces the localization of the tags to plasma membrane/adhesion sites and stress fibers, and reduces the morphotypical effects. Recombinant domains of syntenin with the highest plasma membrane localization display the lowest nuclear localization. Syndecan-1, E-cadherin, β-catenin, and α-catenin colocalize with syntenin at cell-cell contacts in epithelial cells, and coimmunoprecipitate with syntenin from extracts of these cells. These results suggest a role for syntenin in the composition of adherens junctions and the regulation of plasma membrane dynamics, and imply a potential role for syntenin in nuclear processes.